Crescimento físico e desenvolvimento motor em bebês prematuros menores que 1500 gramas acompanhados até os 2 anos - Almeida, Fernanda Gabriella Bezerra de Araujo (2016)
Human development is completed during the first one thousand days after conception, ie during the intrauterine and childhood life. Premature infants are more vulnerable to chronic diseases in adulthood. Insults that lead to changes in growth in early life can result in a permanent deficit in the structure or function of the body in aging, as exemplified by the relationship between the intrauterine growth restriction and the development of metabolic syndrome in adulthood, responsible for a great number of health problems in the elderly population. Objectives: To assess the physical growth and motor development of preterm infants < 1500 g followed by two years of life observing the clinical differences between the groups lower than 1000g and between 1001 and 1500 g. Analyze possible correlations between changes in motor development and abnormal physical growth. Methods: Retrospective cohort study of premature infants who completed the follow-up up to two years of life in an outpatient clinic in southern Brazil. Results: The sample consisted of 82 premature infants, 62.2% female, with an average birth weight of 1127.8 grams, ranging from 460 to 1485 g with a mean gestational age of 29.2 weeks, ranging from 24 to 35 weeks. Atypical motor development was found in 29.3% of children at the end of the 1st semester, 26.8% at the end of the 2nd semester and 16% at the end of the 4th semester. At two years of life, it was detected delayed neurodevelopment in 19.8%, cerebral palsy in 4.9% and hearing loss in 2.4%. Patients with cerebral palsy had lower head circumference during the monitoring. Conclusions: The number of premature infants with growth and developmental impairment decreased during follow-up, probably secondary to rehabilitation treatments, orientations and physical stimulations offered. The relationship between small head circumference and cerebral palsy, and between brain morphology changes and developmental delay, were demonstrated.